ANALISIS SEGMENTASI PASAR BERBASIS MARKETING MIX DALAM MENDUKUNG WISATA KULINER DI EDEN DAILY INTERNATIONAL FOOD DI KOTA SEMARANG - Ahmad Mansur (Lembaga Pengembangan Kinerja Dosen, 2022)
The research carried out has the function of analyzing market segmentation based on marketing mix in supporting culinary tourism at Eden Daily International Food in Semarang City. This research was conducted because this restaurant is considered not maximal in supporting culinary tourism in the city of Semarang seen from the customers who are mostly from within the city of Semarang. With the problem, namely: